Evaluation of the Capacity and the Effectiveness of Covering in Preventing Thoron Exhalation from Earthen Dwelling Materials - Thuy Duong, Nguyen; Thi Anh Nguyet, Nguyen; Hong Quan, Nguyen; Dinh Thai, Nguyen; Thi Dung, Tran; Thi Huyen Trang, Nguyen; Thi Hong, Nguyen; Van Huong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2, 2025)
High indoor thoron (Rn-220) concentrations have been recorded in earthen dwellings in Northern Vietnam, posing potential health risks to residents. No specific medical studies on the health effects of radon gas and its isotopes in indoor environments have been investigated in Vietnam. This study aims to evaluate the capacity and effectiveness of selected surface covering in reducing thoron exhalation from earthen dwelling materials. Earthen walls were simulated using soil bricks made from local construction soil collected in Yen Minh District, with similar geotechnical properties to traditional earth walls. Covering materials were selected based on their availability and affordability. Thoron exhalation rates were determined experimentally by measuring thoron concentration in an accumulation chamber using the SARAD ® RTM 2200 device at two time points: immediately after production and after 18 months of natural exposure. Results indicate that all tested covering materials reduced thoron release to varying degrees. However, the effectiveness of certain materials significantly declined over time, with some losing nearly all barrier function. Among the materials examined, paints and asphalt coatings provided the highest and most stable performance. Wrapping paper combined with common adhesive was identified as a practical, low-cost solution suitable for the socio-economic conditions of earthen dwelling residents.